Can Pakistan replicate the Sri Lankan Counterinsurgency Model used successfully against the Tamil Tigers in its own against insurgents? - Sarmad Ishfaq (Journal of Political Studies, 2017)
Initially, the paper highlights the characteristics adopted in the Sri Lankan counterinsurgency model that was used successfully against the Liberation of Tamil Eelam. The paper aims to ascertain whether it is feasible for Pakistan to apply the model against it insurgent group – Tehreek e Taliban Pakistan. The paper analyses whether Pakistan can reproduce the Sri Lankan model by taking into consideration Pakistan’s environment; kind of insurgency threat; history; politics; allies; and capability of armed forces etcetera. After analysis, it becomes evident that due to certain differences and in both countries’ scenarios and insurgency types, it is simplistic to state that Pakistan should copy the Sri Lankan modus operandi. However, the paper suggests takeaways that need to be appreciated and applied, from the Sri Lankan experience. It is concluded that Pakistan should continue Zarb e Azb; learn lessons from Sri Lanka; and create a “Pakistani model” that is familiar with the country’s needs.